PERAN BADAN USAHA MILIK PETANI DALAM MEWUJUDKAN KEMANDIRIAN PETANI KABUPATEN MAGELANG PASCA PROGRAM BANTUAN BANK DUNIA STUDI KASUS: BUMP PT. MERBABU TUNAS MANDIRI - kelik wahyu nugroho; priyatno harsasto; purwoko . (Journal of Politic and Government Studies, 2016)
This research has a goal to identify the role of a farmer’s organization in the form of farmers owned enterprise in forming farmer’s autonomy after World Bank program assistance in Magelang Regency. It is attempted by FOE through the implementation of agrobusiness agriculture activity whether on farm and off farm. Case study that is used by researcher is FOE PT. Merbabu Tunas Mandiri in Jogonayan Village, Ngablak Subdistrict, Magelang Regency.The type of this research is descriptive analysis through qualitative research. The source of data comes from primary and secondary data. The determining of informant is done through snowball sampling method by determining two types of informant. First informants as the key informants consist of Manager of FOE PT. Merbabu Tunas Mandiri, and farmers. Second informants as triangulation informants consist of BPPKP Magelang Regency, BPTP Central Java, and Yogyakarta Leaf Organic Corporation. In collecting data, researcher uses two methods which are interview and literary study.The problem of the weakness of farmers organization which live and be moved from bottom is often as an obstacle for farmers in following up the government program, so that can not be denied that agriculture development in Indonesia is very slow because there is no following up for the program in society level. Through World Bank assistance program or it is known as Farmer Empowerment through Agricultural Technology and Information (FEATI) an effort for empowering farmers organization starts to be implemented through developing FOE as a form of FEATI contiuous.FOE PT. Merbabu Tunas Mandiri is a Jogonayan Village farmer’s organization which has a goal to increase farmers autonomy after the existing of FEATI through empowering agriculture agrobusiness system. Besides giving encouragement, FOE also gives supporting service for farmers like access service, baking service, agriculture technology implementation service, and information of government policy service. Through the efforts of FOE PT Merbabu Tunas Mandiri, the result shows that the farmer's condition in that area has directed to autonomy, eventhough there are still found many obstacles. In its efforts, FOE is regarded as a place for farmer's actualization, a place for implementing the agriculture technology, a place for absobing employee in rural area, a place for restraining profitable farmer's business activity, and moving the economic cyrcle in rural area.Keywords : FOE, FEATI, Encouragement, Farmers Autonomy, Agrobusiness.